Advancing labour mobility in trade agreements: The lost opportunity in the Trans-Pacific Partnership. Issue 2 (17th June 2019) - Lilly, Meredith B.
Abstract : Purpose: Labour mobility is increasingly recognized as an important component of a globalized international trading system. This paper aims to examine the role of temporary entry commitments in international trade agreements toward facilitating global labour mobility. Design/methodology/approach: This paper traces three decades of temporary entry provisions in international trade agreements signed by the USA and Canada, beginning with their bilateral Canada–US Free Trade Agreement and culminating in the Trans-Pacific Partnership (TPP). Findings: The paper finds that while many countries have continued to liberalize their temporary entry commitments in various trade agreements, the USA has reversed course in the previous decade, hampering international progress. Meanwhile, Canada has pursued ever greater labour mobility provisions with most of its trading partners. Practical implications: The unique roles played by the USA, Canada and other trading partners in advancing a coherent international labour mobility agenda are considered. To continue to advance labour mobility in trade agreements moving forward, policy alternatives to the "all" or "nothing" approaches pursued by Canada and the USA are suggested. Originality/value: To the author's knowledge, this paper is the first to formally evaluate labour mobility in the TPP and the only paper to outline the evolution of temporary entry in the US vs Canadian trade agreements over three decades.